Alemtuzumab improves quality-of-life outcomes compared with subcutaneous interferon beta-1a in patients with active relapsing-remitting multiple sclerosis - Arroyo González, Rafael; Kita, Mariko; Crayton, Heidi; Havrdova, Eva; Margolin, David H; Lake, Stephen L; Giovannoni, Gavin; CARE-MS I and II Investigators (Multiple sclerosis (Houndmills, Basingstoke, England), 2017)
BACKGROUND: Alemtuzumab was superior on clinical and magnetic resonance imaging (MRI) outcomes versus subcutaneous interferon beta-1a in phase 3 trials in patients with relapsing-remitting multiple sclerosis. OBJECTIVE: To examine quality-of-life (QoL) outcomes in the alemtuzumab phase 3 trials. METHODS: Patients who were treatment naive (Comparison of Alemtuzumab and Rebif® Efficacy in Multiple Sclerosis I [CARE-MS I]) or had an inadequate response to prior therapy (CARE-MS II) received annual courses of alemtuzumab 12 mg/day at baseline (5 days) and Month 12 (3 days) or subcutaneous interferon beta-1a 44 µg three times/week. QoL was measured every 6 or 12 months using Functional Assessment of Multiple Sclerosis (FAMS), European Quality of Life-5 Dimensions (EQ-5D) and its visual analog scale (EQ-VAS), and 36-Item Short-Form Survey (SF-36). RESULTS: Statistically significant improvements from baseline with alemtuzumab were observed on all three QoL instruments at the earliest post-baseline assessment and sustained through Year 2. Statistically significant greater QoL improvements over subcutaneous interferon beta-1a were seen at all time points in CARE-MS II with FAMS, EQ-VAS and SF-36 physical component summary, and in CARE-MS I with FAMS. CONCLUSION: Patients treated with alemtuzumab had improvements in physical, mental, and emotional QoL regardless of treatment history. Improvements were significantly greater with alemtuzumab versus subcutaneous interferon beta-1a on both disease-specific and general measures of QoL.
Keywords: Multiple Sclerosis, Relapsing-Remitting; Alemtuzumab; Interferon beta-1a; výsledek terapie; interferon beta 1a; Middle Aged; disease-modifying therapy; mužské pohlaví; Immunologic Factors; Adult; imunologické faktory; kvalita života; alemtuzumab; ženské pohlaví; Humans; CD52 antigen; lidé středního věku; relabující-remitující roztroušená skleróza; dospělí; interferon beta-1a; Female; Quality of Life; quality of life; Treatment Outcome; lidé; Male; multiple sclerosis